SMART ECOTOURISM: UTILIZING THE INTERNET OF THINGS (IOT) FOR EFFICIENT MANAGEMENT OF NATURAL TOURISM AREAS - Murdana, I Made (PT. Hafasy Dwi Nawasena, 2025)
Smart ecotourism represents an emerging paradigm in natural tourism management, integrating Internet of Things (IoT) technologies to enhance environmental monitoring, optimize visitor flow, improve safety, and support sustainable resource use. This article systematically reviewed 91 empirical studies to examine how IoT contributes to smart ecotourism in protected areas, national parks, and community-managed destinations. Findings indicate that IoT significantly strengthens conservation outcomes through real time ecological sensing, reduces trail degradation by managing visitor density, accelerates emergency response via safety devices, and improves operational efficiency through smart energy and waste systems. Successful implementation, however, requires robust governance frameworks, ethical data management, community empowerment, and long term financial planning. The study concludes that IoT can substantially advance sustainable ecotourism when integrated with participatory management and environmentally responsible technological design